PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA QUESTION CARD DISERTAI QR CODE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II SD MUHAMMADIYAH 04 BATU - Tanti Lutfiatul Hidayah; Beti Istanti Suwandayani; Nur Ita Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve the mathematics learning outcomes of grade II elementary school students through the application of the Problem Based Learning (PBL) model assisted by question card media equipped with QR codes. This research used the Classroom Action Research (PTK) approach of the Kemmis and McTaggart model, and involved 30 students of SD Muhammadiyah 04 Batu. The research was conducted in two cycles with the stages of planning, implementation, observation, and reflection. The instrument used was a written test that focused on the cognitive domain. The results showed a significant increase in learning outcomes from pre-cycle to cycle II. The average student score increased from 59.2 in the pre-cycle to 71.5 in cycle I, and 82.3 in cycle II. The percentage of student learning completeness also increased from 30% in the pre-cycle to 57% in cycle I, and 83% in cycle II. The question card media equipped with QR codes provides easy access to question explanations and increases interactivity in learning. Thus, the combination of PBL model and innovative media proved effective in improving students' mathematical understanding and engagement.